2021
DOI: 10.52337/pjer.v4i2.128
|View full text |Cite
|
Sign up to set email alerts
|

Performance Based Professional Development of in-Service Teachers

Abstract: Developing countries all over the world are struggling to improve their education system to achieve sustainable development standards. Pakistan being a developing country is no different; the two major issues related to education are quality and quantity and both are imperative in our current situation where we are up against the challenges of low literacy and poor quality of education. The government has taken up the challenge of low quality of education by investing in teacher education in the form of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Developing countries are struggling in improving the educational standards. Likewise, Pakistan also struggling to improve the quality of education standard and provide training to in-service teachers, this step will help in improving performance indicators of teachers and ensure to produce competent in-service teachers (Rizwan, 2021) 2020) research findings also revealed the training needs of in-service teachers and stressed to provide CPD opportunities in Pakistan, so that professionals communication and technological literacy skills will be improved. Research literature also revealed the positive impact of CPD programmes in the Pakistani context (Aslam, 2013;Dilshad et al, 2019;Mahmood & Iqbal, 2010;Nasreen & Odhiambo, 2018;Saleem et al, 2014;Shah et al, 2015;Singh et al, 2020).…”
Section: Need Of In-service Teachers Training and Continuous Professi...mentioning
confidence: 99%
“…Developing countries are struggling in improving the educational standards. Likewise, Pakistan also struggling to improve the quality of education standard and provide training to in-service teachers, this step will help in improving performance indicators of teachers and ensure to produce competent in-service teachers (Rizwan, 2021) 2020) research findings also revealed the training needs of in-service teachers and stressed to provide CPD opportunities in Pakistan, so that professionals communication and technological literacy skills will be improved. Research literature also revealed the positive impact of CPD programmes in the Pakistani context (Aslam, 2013;Dilshad et al, 2019;Mahmood & Iqbal, 2010;Nasreen & Odhiambo, 2018;Saleem et al, 2014;Shah et al, 2015;Singh et al, 2020).…”
Section: Need Of In-service Teachers Training and Continuous Professi...mentioning
confidence: 99%
“…In the modern era, the demand of the professional teacher has a great significance in fulfilling the requirement of the learning process. The lack of professional skills produces incompetent human capital (Siddiqui, 2010;2021). Moreover, at the government level, it has been seen lack of consciousness regarding in-service training.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…The learning process can be successful if the management activities implement efficiently, such as; discipline, taking care of students' movement and cleanliness of tangibles infrastructure. Therefore, teaching training is the basic need of the teaching faculty for the successful completion of the institutional objectives (Rizwan, 2021). The positive interaction between teacher and students in a class plays a significant contribution to conducting the teaching process.…”
Section: Review Of the Related Literaturementioning
confidence: 99%